Kemampuan Deskripsi Kemampuan Berpikir Kreatif Matematis Siswa Pada Materi Teorema Pythagoras Ditinjau Dari Self-Concept Matematis Siswa Kelas VIII Di SMP Negeri 1 Kabila: Kemampuan Berpikir Kreatif ditinjau dari Self-Concept - Chacha Anggriani Tuli; Khardiyawan A.Y Pauweni; Bertu Rianto Takaendengan (Mandalika Mathematics and Educations Journal, 2025)
Mathematics not only functions as a discipline of calculation but also serves as a medium to develop students’ critical and creative thinking skills. This study aims to describe the mathematical creative thinking ability of eighth-grade students at SMP Negeri 1 Kabila on the Pythagorean Theorem material in terms of their mathematical self-concept. The research was conducted in the first semester of the 2024/2025 academic year using a descriptive method with a qualitative approach. The subjects consisted of six students selected through purposive sampling, representing high, medium, and low categories of self-concept. Data were collected through mathematical creative thinking tests and interviews, then analyzed based on the indicators of fluency, flexibility, and originality. The results showed that students with a high self-concept fulfilled all indicators and were categorized as highly creative, students with a medium self-concept met only part of the indicators and were categorized as creative to fairly creative, while students with a low self-concept struggled to meet the indicators and were categorized as not creative. These findings emphasize that the higher the students’ mathematical self-concept, the better their mathematical creative thinking ability.